Learning outcomes with the application of product based entrepreneurship module in vocational higher education - Asmar Yulastri; Hendra Hidayat; Ganefri Ganefri; Fuji Edya; Syaiful Islami (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This paper aims to explore and explain the application entrepreneurship module based products in higher vocational education. Methods of the development of this research using stages of Analysis, Design, Development, Implementation (ADDI). Subjects were students who are taking entrepreneurship courses in higher vocational education. The technique of data analysis was the learning outcomes of the application of product based entrepreneurship module which consisted of, (1) the results of the cognitive aspects of learning achievement test used in the form of multiple-choice tests; (2) the study results in the affective aspects obtained from the measurement results against predefined criteria, with special sections that assess students' attitude during the process and attitude of learning, particularly in the work of making a product; (3) the results of study on psychomotor aspect views from the observation of activities and work activities done by the students. Based on cognitive aspects of learning outcomes for entrepreneurial learning showed that test before using the product based entrepreneurship modules have an average of learning outcomes is quite effective and after using the product based entrepreneurship modules have an average is the effective category. The average results of student learning in psychomotor and affective aspects before using the module are quite effective and after using the product based entrepreneurship module psychomotor and affective aspects have an average result of learning is very effective. It can be concluded that learning with product based entrepreneurship module can improve student learning outcomes in higher vocational education.